Model Regresi Dummy Indeks Prestasi Akademik Mahasiswa Program Studi Matematika Faperta Unimor - Grandianus Seda Mada; Nugraha K. F. Dethan; Faustianus Luan (Program Studi Matematika, Universitas Timor, 2023)
One indicator that can be used as a determinant in the quality of higher education is the academic achievement of students. Grade Point Average (GPA) is a measure of the academic performance. GPA gained students can not be separated from the quality of the incoming student input at the college. This study discusses some of the indicators that can be used as a measure of the quality of student input from the academic side, such as the National Examination (NE), the origin of school (public / private), gender and type of college entrance exam (SNMPTN test, SBMPTN test and independent institution test). Because some of these indicators are qualitative so the data analysis used regression analysis with dummy variables. Research conducted on students of Mathematics Study Program, Faculty of Agriculture, Timor University, class of 2017 to class of 2021. From the data processing, obtained regression model: . From the data analysis, concluded that the female students of Mathematics Study Program, Faculty of Agriculture, Timor University, coming from public schools and type of college entrance exam is SNMPTN have the greatest tendency to obtain high GPA compared with other students. In addition, for the regression equation obtained above was 38.2% means that the independent variable in the model can explain the diversity of the GPA of 38.2%.